Phytofabrication and characterization of Alchornea cordifolia silver nanoparticles and evaluation of antiplasmodial, hemocompatibility and larvicidal potential - Kojom Foko, Loick Pradel; Hawadak, Joseph; Verma, Vaishali; Belle Ebanda Kedi, Philippe; Eboumbou Moukoko, Carole Else; Kamaraju, Raghavendra; Pande, Veena; Singh, Vineeta (Frontiers in Bioengineering and Biotechnology, 2023)
Purpose: The recent emergence of Plasmodium falciparum (Pf) parasites resistant to current artemisinin-based combination therapies in Africa justifies the need to develop new strategies for successful malaria control. We synthesized, characterized and evaluated medical applications of optimized silver nanoparticles using Alchornea cordifolia (AC-AgNPs), a plant largely used in African and Asian traditional medicine. Methods: Fresh leaves of A. cordifolia were used to prepare aqueous crude extract, which was mixed with silver nitrate for AC-AgNPs synthesis and optimization. The optimized AC-AgNPs were characterized using several techniques including ultraviolet-visible spectrophotometry (UV-Vis), scanning/transmission electron microscopy (SEM/TEM), powder X-ray diffraction (PXRD), selected area electron diffraction (SAED), energy dispersive X-ray spectroscopy (EDX), Fourier transformed infrared spectroscopy (FTIR), dynamic light scattering (DLS) and Zeta potential. Thereafter, AC-AgNPs were evaluated for their hemocompatibility and antiplasmodial activity against Pf malaria strains 3D7 and RKL9. Finally, lethal activity of AC-AgNPs was assessed against mosquito larvae of Anopheles stephensi, Culex quinquefasciatus and Aedes aegypti which are vectors of neglected diseases such as dengue, filariasis and chikungunya. Results: The AC-AgNPs were mostly spheroidal, polycrystalline (84.13%), stable and polydispersed with size of 11.77 ± 5.57 nm. FTIR revealed the presence of several peaks corresponding to functional chemical groups characteristics of alkanoids, terpenoids, flavonoids, phenols, steroids, anthraquonones and saponins. The AC-AgNPs had a high antiplasmodial activity, with IC50 of 8.05 µg/mL and 10.31 µg/mL against 3D7 and RKL9 Plasmodium falciparum strains. Likewise, high larvicidal activity of AC-AgNPs was found after 24h- and 48h-exposure: LC50 = 18.41 µg/mL and 8.97 µg/mL (Culex quinquefasciatus), LC50 = 16.71 µg/mL and 7.52 µg/mL (Aedes aegypti) and LC50 = 10.67 µg/mL and 5.85 µg/mL (Anopheles stephensi). The AC-AgNPs were highly hemocompatible (HC50 > 500 µg/mL). Conclusion: In worrying context of resistance of parasite and mosquitoes, green nanotechnologies using plants could be a cutting-edge alternative for drug/insecticide discovery and development.